RANCANG BANGUN ALAT BANTU PEMOTONGAN SEGI ENAM PADA MESIN BUBUT KONVENSIONAL UNTUK MENINGKATKAN AKURASI DAN EFISIENSI PROSES PRODUKSI - Priyanto, Sugeng; Lubi, Ahmad; Anggrainy, Rani; Hari Krisyono , Danar; Muhamad Yusup , Fahmi (Universitas Nusa Putra, 2024)
The development of manufacturing technology, including in the field of lathes, continues to progress quite significantly to meet increasingly complex industrial needs. One of the important innovations in lathes was the use of detachable heads, the use of cutting tools in a more flexible and efficient way. Bolts with hexagonal holes are an important component in the automotive world, one of their uses is in motorbike calipers. After conducting a literature study regarding loose heads and drill chucks on lathe machines, the author carried out an evaluation and carried out a design for the design of an internal hexagon rotating tool on a conventional lathe using the Inventor application. Evaluation of the performance of this tool shows that this tool can be relied on for practical and educational applications, and meets the needs of its users which can be seen in the Von Mises Stress simulation results and also the results of tool testing